Perancangan Sistem Informasi Pelaporan Barang Masuk dan Keluar Atk pada FPIPS UPI - Dwi Yuliansyah Kusnadi; Rika Rahmawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to understand the reporting of incoming and outgoing goods because the existing system is not well computerized, relying heavily on Microsoft Excel, leading to many challenges. In the context of the business world, computers as data tools are an appropriate means to process every business transaction. Because manual documentation is no longer feasible due to the increasing volume of transactions, it significantly affects office stationery inventory. Therefore, a software application has become a vital necessity for every organization or company to streamline its business operations. With computerization, data processing becomes more effective, secure, minimizes errors, and archives can be organized neatly. To ensure the smooth operation of the system, the author attempts to design a system for office stationery inventory management. Currently, the author uses the PHP programming language, primarily focusing on inventory management programs. In designing this system, the author creates input designs that outline the office stationery data processes.